2015
DOI: 10.3109/15563650.2015.1112907
|View full text |Cite
|
Sign up to set email alerts
|

Flubromazolam – A new life-threatening designer benzodiazepine

Abstract: Flubromazolam is a new designer drug. Recreational use may be a cause of prolonged, severe intoxication associated with coma, hypotension, and rhabdomyolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 7 publications
0
56
0
Order By: Relevance
“…Benzodiazepines were misused long before emerging as NPS and a recent report highlighted the increasing illicit availability and misuse of a clinically used benzodiazepine, alprazolam, often purchased from the dark web . The NPS benzodiazepines (referred to in this work as NPS‐benzodiazepines) have already been reported in a number of overdose cases, driving under the influence of drugs (DUID) cases, and hospital admissions . The lack of control over and safety of these NPS‐benzodiazepines is a prevalent issue and it is predicted that it will become an even more worrying trend as their misuse continues to spread.…”
Section: Introductionmentioning
confidence: 99%
“…Benzodiazepines were misused long before emerging as NPS and a recent report highlighted the increasing illicit availability and misuse of a clinically used benzodiazepine, alprazolam, often purchased from the dark web . The NPS benzodiazepines (referred to in this work as NPS‐benzodiazepines) have already been reported in a number of overdose cases, driving under the influence of drugs (DUID) cases, and hospital admissions . The lack of control over and safety of these NPS‐benzodiazepines is a prevalent issue and it is predicted that it will become an even more worrying trend as their misuse continues to spread.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Recently, a case of intoxication of flubromazolam indicated that low plasma concentrations around 0.043 mg/L can cause a deep coma with long-lasting central nervous system-depression. [6] According to online drug users' forums, flubromazolam is a drug with high potency and long duration of action (up to 3 d), with reported user's dose ranging from 0.25 mg on blotters up to 16 mg in tablets for users with high self-reported benzodiazepine tolerance. [7,8] In one reported in vitro study using pooled human liver microsomes (pHLM), one mono and one dihydroxylated metabolite of flubromazolam were tentatively identified, however without assigning the site of the monohydroxylation.…”
Section: Flubromazolam Was First Reported In Sweden In 2014 and Inclumentioning
confidence: 99%
“…7,14 Norflurazepam, also named desalkykflurazepam, is the principal active metabolite of flurazepam, 10,17,18 a BZ hypnotic used in the United States since 1970. 6,[28][29][30][31] In cases of overdose, some designer BZs can be detected with adequate sensitivity by immunoassay-based urine drug screening. 10,21 The principal determinants of elimination 10 This scenario is not difficult to envision if a user is not familiar with a particular compound, or ingests an impure mixture of multiple compounds.…”
Section: Designer Benzodiazepines: a Review Of Published Data And Pubmentioning
confidence: 99%